Efficacy and Safety of an Intravenous C1-Inhibitor Concentrate for Long-Term Prophylaxis in Hereditary angioedema. Issue 1 (March 2017) - Craig, Timothy; Shapiro, Ralph; Vegh, Arthur; Baker, James W.; Bernstein, Jonathan A.; Busse, Paula; Magerl, Markus; Martinez-Saguer, Inmaculada; Riedl, Marc A.; Lumry, William; Williams-Herman, Debora; Edelman, Jonathan; et al.
Background: The plasma-derived, pasteurized, nanofiltered C1-inhibitor concentrate (pnfC1-INH) is approved in the United States as an intravenous (IV) on-demand treatment for hereditary angioedema (HAE) attacks, and, in Europe, as on demand and short-term prophylaxis. Objective: This analysis evaluated Berinert Patient Registry data regarding IV pnfC1-INH used as long-term prophylaxis (LTP). Methods: The international registry (2010–2014) collected prospective and retrospective usage, dosing, and safety data on individuals who used pnfC1-INH for any reason. Results: The registry included data on 47 subjects (80.9% female subjects; mean age, 44.8 years), which reflected 4082 infusions categorized as LTP and a total of 430.2 months of LTP administration. The median absolute dose of pnfC1-INH given for LTP was 1000 IU (range, 500–3000 IU), with a median time interval between infusion and a subsequent pnfC1-INH–treated attack of 72.0 hours (range, 0.0–166.4 hours). Fifteen subjects (31.9%) had no pnfC1-INH–treated HAE attacks within 7 days after pnfC1-INH infusion for LTP; 32 subjects (68.1%) experienced 246 attacks, with rates of 0.06 attacks per infusion and 0.57 attacks per month. A total of 81 adverse events were reported in 16 subjects (34.0%) (0.02 events per infusion; 0.19 events per month); only 3 adverse events were considered related to pnfC1-INH (noncardiac chest pain, postinfusion headache, deep vein thrombosis in a subject with an IV port). Conclusion: In this international registry, IV pnf-C1-INH given as LTP for HAE was safe and efficacious, with a low rate of attacks that required pnfC1-INH treatment, particularly within the first several days after LTP administration.